Model Integrasi Sains dan Agama dalam Pendidikan Nasional - Muhammad Miftah (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2017)
Religious education in elementary schools so far only serves as a complement of the learning process. The attention and commitment of the government in developing religious education is still limited in fulfilling the obligations of the existing laws and regulations. Themes that are presented in the 2013 Integrative Thematic Curriculum provide new hope in the learning of religious education which will be juxtaposed with other subjects in the learning process. The 2013 Curriculum was created due to the deviant behavior among learners ranging from moral decline and loss of ethics of Indonesian students. New breakthrough in the 2013 Curriculum is expected to answer various social problems that have long proliferated in the world of education. In this paper, we try to reveal the model of religious integration with the existing science in the new curriculum which can be found from the unification of the subject matter through the integration of the basic competencies of each subject into a theme related to nature and environment in everyday life. The subject matter is broke down into several themes which are expected to enable students to understand the subject matter holistically or comprehensively and not partially (piece by piece).